Pengembangan Media “CAKU” (CAri aKU) dan Lembar Kerja Peserta Didik (LKPD) untuk Meningkatkan Pemahaman Himpunan di Kelas VII - Sari, Noviana Puspita; Tyaningsih, Ratna Yulis (FKIP Universitas Mataram, 2024)
This research aims to develop interactive learning media CAKU and Student Worksheets (LKPD) to improve students' understanding of set material in class VII. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The analysis stage involves identifying needs and problems in learning set material. The design stage focuses on designing media and LKPD that suit the characteristics of class VII students. In the development stage, the media was prepared and tested on a small scale through peer teaching in the Innovative Mathematics Learning Study class which was attended by 16 students to obtain input and improvements. Implementation is carried out through field trials to measure the effectiveness of the media and LKPD that have been developed. Evaluation is carried out to assess the increase in students' understanding before and after using the learning media. The research results show that learning media is effective in increasing students' understanding of the concept of set. Apart from that, it is considered interesting and motivating for students to learn, thus making the learning process more interactive and fun. Thus, it is hoped that the development of the learning media CAKU and LKPD can become an innovative alternative tool for educators in teaching set material, as well as improving the quality of learning in class VII.